2017
DOI: 10.7202/1046505ar
|View full text |Cite
|
Sign up to set email alerts
|

Maintien à domicile : capacité d’offre de services communautaires actuels et futurs au Nouveau-Brunswick

Abstract: La présente étude comporte trois objectifs : 1) déterminer l’état actuel des services offerts pour le maintien à domicile; 2) explorer la nature de la planification des services futurs pour le maintien à domicile; et 3) exposer les défis reliés aux services et les moyens qui s’offrent aux organismes pour que les services répondent le plus efficacement possible aux besoins des personnes âgées francophones. De type séquentiel exploratoire mixte, cette étude a permis de recueillir des données qualitatives pour bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, community organizations have struggled to recruit bilingual employees, and the retention of employees in general has proved to be problematic due to working conditions. Another recent study conducted by The´riault and Dupuis-Blanchard (2017) paints a worrying picture of the future workforce that will provide services to older adults in the community. The study finds that current employees had a mean age of 50 among the mainly female workers hired to provide home support services, and that few workers were under 30 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, community organizations have struggled to recruit bilingual employees, and the retention of employees in general has proved to be problematic due to working conditions. Another recent study conducted by The´riault and Dupuis-Blanchard (2017) paints a worrying picture of the future workforce that will provide services to older adults in the community. The study finds that current employees had a mean age of 50 among the mainly female workers hired to provide home support services, and that few workers were under 30 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…The study finds that current employees had a mean age of 50 among the mainly female workers hired to provide home support services, and that few workers were under 30 years of age. Compensation is not far above the minimum wage, and the vast majority of workers must use their personal vehicle, often without being reimbursed for travel between clients (The´riault & Dupuis-Blanchard, 2017). Solutions are thus necessary to address the human resources needs of the aging francophone population but also the broader issue of the shortage of labor force in the home support sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the current pandemic crisis has mostly highlighted the many challenges faced by health professionals caring for older adults in LTCFs, a career in aging can take diverse forms within or outside of healthcare and can be a very rewarding career path. A recent study conducted in Eastern Canada confirmed that community organisations serving older adults have a reason to worry: in addition to recruitment and retention challenges, much of their workforce was near the age of retirement (Thériault & Dupuis‐Blanchard, 2017). These service organisation administrators reported difficulty recruiting and retaining bilingual employees, who find employment with better working conditions elsewhere.…”
Section: Introductionmentioning
confidence: 99%